2011
DOI: 10.4314/ajfand.v11i1.65877
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of economic efficiency in cocoa production in Ghana

Abstract: 4508 ABSTRACTThe main purpose of this study was to analyze the economic efficiency of resource utilization in cocoa production of the cocoa farmers in Ghana to provide information for effective application and management of farm inputs on cocoa farms and policy recommendation. A random sample of 300 farmers in the Eastern, Ashanti, BrongAhafo, Central, Volta and Western regions of Ghana were selected, using the multistage sampling approach. Individual farmers were interviewed by using questionnaires. Descripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 4 publications
1
18
0
Order By: Relevance
“…These researchers had shown that the increase in pesticide quantities in cocoa fields in the Offinso district of Ghana had a positive effect on cocoa production. In addition, a study conducted in Ghana by Aneani and al., [22] revealed similar results that cocoa farm size, quantity of insecticides and quantity of fungicides were 0.514, 0.273 and 0.090 respectively.…”
Section: Discussionsupporting
confidence: 70%
“…These researchers had shown that the increase in pesticide quantities in cocoa fields in the Offinso district of Ghana had a positive effect on cocoa production. In addition, a study conducted in Ghana by Aneani and al., [22] revealed similar results that cocoa farm size, quantity of insecticides and quantity of fungicides were 0.514, 0.273 and 0.090 respectively.…”
Section: Discussionsupporting
confidence: 70%
“…In other related work by Aneani et al (2011), they found that age of farmers greatly influence cocoa output in Ghana. The authors recommend greater involvement of young households in farming activities to help increase cocoa output.…”
Section: Determinants Of Production Efficiencymentioning
confidence: 89%
“…The inefficiency effect model can only be estimated if the efficiency effects are present. Given that is present in the model it implies that it is justifiable to employ the SFA as similarly argued by Aneani et al (2011). In this study, Battesse and Coelli (1995) and Coelli (1996) models were used to specify the stochastic frontier function with behavior inefficiency components and used to estimate all parameters together in one step maximum likelihood estimation.…”
Section: Specification Of the Empirical Modelmentioning
confidence: 99%